2012
DOI: 10.1103/physrevd.85.124020
|View full text |Cite
|
Sign up to set email alerts
|

Fitting galactic rotation curves with conformal gravity and a global quadratic potential

Abstract: We apply the conformal gravity theory to a sample of 111 spiral galaxies whose rotation curve data points extend well beyond the optical disk. With no free parameters other than galactic mass to light ratios, the theory is able to account for the systematics that is observed in this entire set of rotation curves without the need for any dark matter at all. In previous applications of the theory a central role was played by a universal linear potential term V (r) = γ 0 c 2 r/2 that is generated through the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
208
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(229 citation statements)
references
References 93 publications
(126 reference statements)
8
208
0
Order By: Relevance
“…We compiled 110 observed galaxies (de Blok & Bosma 2002;Swaters et al 2003;de Blok et al 2004;Kuzio de Naray et al 2008;de Blok et al 2008;Swaters et al 2009;Oh et al 2011;Mannheim & O'Brien 2012;Oh et al 2015, and references therein) with Vmax<150kms −1 that have rotation curves that allow us to compare Vrot(1kpc) with Vmax.…”
Section: Observationsmentioning
confidence: 99%
“…We compiled 110 observed galaxies (de Blok & Bosma 2002;Swaters et al 2003;de Blok et al 2004;Kuzio de Naray et al 2008;de Blok et al 2008;Swaters et al 2009;Oh et al 2011;Mannheim & O'Brien 2012;Oh et al 2015, and references therein) with Vmax<150kms −1 that have rotation curves that allow us to compare Vrot(1kpc) with Vmax.…”
Section: Observationsmentioning
confidence: 99%
“…) last seems to be of order one, for now over 200 galaxies [3][4][5][6] fit by the theory. This universality found in the last data point of each galaxies centripetal acceleration (scaled here to 1 c 2 ) provides argument for the recent work of McGaugh 7 et al, and this phenomena will be explored in more detail below.…”
Section: Rotation Curves Of the Whisp Surveymentioning
confidence: 82%
“…In recent years, Mannheim and O'Brien have shown that conformal gravity can be used to accurately describe the rotation curves of a diverse set of galaxies without the need to invoke dark matter. [3][4][5][6] Since all attempts to find any direct evidence of dark matter have been unsuccessful so far, alternative theories of gravity have become increasingly worth considering as an explanation for phenomena ascribed to dark matter. Its success in fitting galactic rotations makes conformal gravity an ideal candidate to explore in an effort to theoretically describe these additional effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be fascinating to put a full-fledged quantization of gravity in this scheme, and even if this is still far in the future, we note that possible stating points could be conformal gravity, especially in the Bender-Mannhiem formalism [47][48][49], which leads to unitary and renormalizable theory of gravity [50] and has interesting astrophysical consequences [51,52]. Interesting connections between conformal and Einstein gravities are discussed in Ref.…”
mentioning
confidence: 95%